The Effects of Local Aquatic Activities on Coral Cover in the Jordanian Gulf of Aqaba - Omar Attum; Mohammad Al Tawaha; Zachary Giuffre; Ehab Eid; Abdullah Abu Awali (Turkish Journal of Bioscience and Collections)
Objective: The reef flats at the Gulf of Aqaba, Jordan, are exposed to the accelerated development associated with increased interest in recreational marine activities such as diving and snorkeling. The physical damage from net entanglement and overfishing has also affected the coral reef. This research evaluated the effects of aquatic, commercial, and land-based activities on the total coral cover in the Aqaba Marine Park (Now the Aqaba Marine Reserve) and the power station located north of the reserve.Materials and Methods: The line transect method was used to estimate the coral cover, followed by measuring the distance of the 13 diving sites to the different landscape disturbances and applying a linear regression analysis.Results: The results showed no significant relationship between the distance to the nearest human disturbance and the entire coral cover in the depth categories. In addition, there was no significant difference between low and high-frequency diving pressure and the mean coral cover at any depth category and no significant difference in the mean coral cover between low and high-frequency snorkeling sites. Sites with higher fishing activity had significantly lower coral cover than sites with lower fishing activity. However, there was no significant difference in the mean coral cover between sights with higher and lower fishing activity at the 21-30 m depth range.Conclusion: The study illustrated that local marine recreational activities (diving and snorkeling) do not affect the coral cover structure up to 10 meters depths. However, considerable coral degradation was found in high fishing zones less than 10 meters deep, which correlates with illegal fishing activities. We believe illegal fishing has negatively affected the coral cover, and recreational marine activities reduced coral cover, especially in diving areas requiring shore entrance.